Postprocedural delirium following mechanical thrombectomy for acute ischemic stroke: a retrospective study - Sachdev, Alisha; Torrez, Daniel; Sun, Sarah; Michapoulos, George; Rigler, Nicholas C.; Feldner, Alexandra L.; Hong, Young Soo; McCarthy, Robert J. (Frontiers in Anesthesiology, 2024)
Introduction: Nationally representative estimates on in-hospital delirium after acute ischemic stroke are not well established and there is limited data on the impact of delirium on clinical outcomes following mechanical thrombectomy. We evaluated risk factors for delirium and the impact on outcomes following mechanical thrombectomy for an acute ischemic stroke.: A retrospective study of patients that underwent mechanical thrombectomy for acute ischemic stroke at a single tertiary comprehensive stroke center between April 2011 and Dec 2019. Delirium was assessed using the Confusion Assessment Method for the Intensive Care Unit. Patient characteristics, comorbidities, laboratory data, elapsed times, tissue plasminogen activator use, duration of the procedure, type of anesthesia, National Institute of Health stroke scores (NIHSS), sedation scores, reperfusion grades, complications, length of hospital stay, discharge disposition and 90-day mortality were evaluated.Results: Five hundred two patients were evaluated, and post-procedural delirium was identified in 24/467 (5.1%). patients. Thirty-five patients could not be assessed for delirium due to excessive sedation. The incidence of delirium in white versus non-white patients <65 years was 5/137 (3.6%) compared with 0/91 (0%), and 7/176 (4.0%) compared 12/63 (19%) in patients ≥65 years, P=0.006. Bias reduction multi-variable analysis identified low postprocedural hemoglobin level odds ratio 0.76 (95% CI 0.61 to 0.92, P=0.006), greater age (odds ratio 1.04, 95% CI 1.01 to 1.009, P=0.024) and non-white race odds ratio 2.52 (95% CI 1.06 to 6.38, P=0.030) as factors associated with delirium (Brier score = 0.045, C-index = 0.800, Akaike Information Criterion (AIC) = 174). General anesthesia was not associated with an increased delirium risk. NIHSS at 24,48 hours and at discharge, length of stay and 90-day mortality were not different between delirium and non-delirium groups. Delirium patients had reduced odds ratio 0.13 (05% CI 0.01 to 1.00, P=0.02) for home discharge.Discussion: Delirium following mechanical thrombectomy for acute ischemic stroke primarily affected older patients and was associated with reduced odds for home discharge following hospitalization. Changes in NIHSS during hospitalization and 90-day mortality were not adversely affected by the presence of delirium. General anesthesia was not associated with an increased delirium risk following mechanical thrombectomy.